Batik Cloth and Ecosufism in Pekalongan City: Maintaining Tradition and Natural Balance? - Hermawan, Raji; Zulfa, Nadhifatuz (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2023)
Pekalongan City, known as the center of world batik, presents cultural richness through the art of batik cloth. This article aims to explore the relationship between batik cloth production and the concept of ecosufism in Pekalongan, revealing how and whether local traditions can be in line with sustainability thinking in maintaining the balance of nature. This research is a literature study and exploration in the field, with data collection techniques in the form of literacy studies, field observations and documentation, while data analysis techniques use data reduction, data presentation and drawing conclusions. The results of the research: the ecosophistic behavior of the Pekalongan batik craftsmen community has begun to fade, as indicated by the existence of batik production that does not pay attention to environmental sustainability in the form of batik waste pollution in the rivers of Pekalongan city. This is in contrast to the principles in ecosufism which link a servant's close behavior and direct experience with God accompanied by maintaining ecological sustainability and preserving nature. It also contrasts with the characteristics of religious batik craftsmen. On the other hand, traditional Pekalongan batik cloth has a meaning of great spirituality, one of which is the typical Pekalongan batik motif, namely Jlamprang. Jlamprang has a symbolic meaning of the relationship between the human world and the divine world. This meaning also contrasts with the waning ecosufism of batik craftsmen. The hope is that with this research, the community, especially batik craftsmen, will be able to re-cultivate the spirit of ecosufism in producing batik cloth, thereby creating harmony in the relationship between creatures and their Khaliq, as well as the relationship between humans and the natural surroundings. In fact, humans as Allah's caliphs on earth are servants of Allah who not only have a good relationship with the Khaliq, but also have a good relationship with His creatures, including the universe created by Allah SWT.